(untitled) (La U Investiga, 2021)
Introduction: Exclusive breastfeeding is necessary for the feeding, nutrition and wellbeing of the child. For decades worldwide there has been the premature abandonment of this elementary practice that directly affects the growth and integral development of the child. Objective: To identify the socio-demographic components that affect exclusive breastfeeding. Materials and methods: The study has a descriptive, crosssectional design, a structured and validated survey was applied to 419 mothers using stratified probability sampling of a total population of 3000 lactating mothers from Zone 1 of Ecuador calculated with 95% confidence and 5% error; the variables are sociodemographic characteristics, which included age, ethnicity, occupation, related to the time of exclusive breastfeeding. Results: The mestizo ethnic group predominates with 43.4%; In general, 41.5% fed EBF up to six months, with indigenous women standing out with 47.1% as the ethnic group that maintains this practice. Regarding age, mothers over 35 years of age, which corresponds to 53.2%, exceed adolescents and young women in compliance with WHO recommendations, while 42.2% of non-working mothers provide breastfeeding. Conclusions and Recommendations: Exclusive breastfeeding has been affected mainly by maternal age, the younger the mother, the more likely abandonment is, according to ethnicity, indigenous women give more breastfeeding followed by Afro-descendants and mestizos. The implementation of relactation could be a strategy for the integral development of the child.